2011
DOI: 10.5858/2010-0204-oa.1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Implications of Margin Involvement by Pleomorphic Lobular Carcinoma In Situ

Abstract: Context.—The appropriate treatment for patients with pleomorphic lobular carcinoma in situ (PLCIS) is unknown. When diagnosed on core biopsy, excision is recommended; however, management of PLCIS when it involves margins has not been addressed. Objective.—To evaluate the significance of PLCIS that is located close to, or at, a resection margin. Design.—We identified 26 patients with resection specimens containing PLCIS, all of whom were offered chemoprevention and radiation therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Studies of non-classical LCIS have reported up to 50% finding of a more significant lesion on excision [32,33]. Recurrence rates following local excision range from 0 to 57% [34][35][36][37]. Zhong et al observed recurrence rates of 18% and 28% in apocrine pLCIS and pLCIS respectively [31].…”
Section: Apocrine Lobular Carcinoma In Situmentioning
confidence: 99%
“…Studies of non-classical LCIS have reported up to 50% finding of a more significant lesion on excision [32,33]. Recurrence rates following local excision range from 0 to 57% [34][35][36][37]. Zhong et al observed recurrence rates of 18% and 28% in apocrine pLCIS and pLCIS respectively [31].…”
Section: Apocrine Lobular Carcinoma In Situmentioning
confidence: 99%
“…PLCIS is further classified into 1) non-apocrine and 2) apocrine (Chen et al, 2009). Mammographic results have shown that the solid pattern of PLCIS shows significant Pleomorphic calcification (Downs-Kelly et al, 2011;Khoury et al, 2014;Pieri et al, 2014;De Brot et al, 2017). Although the BMI does not affect LSIC, breast density does.…”
Section: Breast Cancermentioning
confidence: 99%